1982
DOI: 10.1055/s-0038-1657254
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Treatment of Deep Leg Vein Thrombosis with Porcine Plasmin and Low Dose Streptokinase

Abstract: SummarySequential treatment of deep leg vein thrombosis with porcine plasmin and low dose streptokinase (10,000-20,000 U/h) produces strong systemic fibrinolysis as demonstrated by the sustained decrease of euglobulin lysis time, of thromboplastin time values in percent, fibrinogen and factor V levels. There is a statistically significant negative correlation between thrombolytic results and euglobulin lysis time. Treatment periods below 3 days are unlikely to give satisfactory results. Occluded vein segments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1984
1984
1998
1998

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…PLG depletion may occur more rapidly with the high dose SK schedule (14). It has been previously shown, that a prolonged lytic state with fibrinogen values less than 0.8 g/1 may favour throm bolytic success (2,15). On the other hand severe bleeding complications -at least in patients with arterial occlusions -may also be more frequent and hence p-PL pretreatment has been abandoned for this indication (3).…”
Section: Discussionmentioning
confidence: 99%
“…PLG depletion may occur more rapidly with the high dose SK schedule (14). It has been previously shown, that a prolonged lytic state with fibrinogen values less than 0.8 g/1 may favour throm bolytic success (2,15). On the other hand severe bleeding complications -at least in patients with arterial occlusions -may also be more frequent and hence p-PL pretreatment has been abandoned for this indication (3).…”
Section: Discussionmentioning
confidence: 99%
“…Our successive treatment series with SK alone or combined with plasmin 48 clearly showed a rela tionship between intensity of fibrinolysis, success rate, and, unfortunately, bleeding complications. 49 It was expected that the anisoyl-protected SK-Plg complex (BRL 26,921, Beecham) would con siderably reduce the fibrinolytic effect in circulating blood.…”
Section: Dvt Treatment Schemesmentioning
confidence: 70%
“…How ever, there is no doubt that plasmin infusion has a much slower thrombolytic action than SK, but it can be a very helpful complement to both SK and UK treatment. 48 ' 50 More recently there have been attempts to localize the fibrinolytic action to the thrombus and to make it more specifically thrombolytic. Two ap proaches are possible: (1) to use the affinity for fibrin of acylated SK-Plg complexes or of the extrinsic (tissue) plasminogen activator.…”
Section: Comparison Of the Different Fibrinolytic Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…These rates of thrombolysis are similar to those obtained with U K by Niessner et al (10), who found no differences in the rates of lysis in patients treated with doses ranging from 700 to 2100 U/kg/h administered for 7 days. It has been suggested by some authors that the rate of lysis might be positively correlated with the duration of the thrombolytic treatment with UK (5, 7) or streptokinase (21,22), but other authors did not see any advantage from prolonging therapy beyond 3 days (23)(24)(25). Our comparison of two treatment regimens with an equal maintenance dose of UK (2500 U/kg/h) administered for 3 or 7 days showed that lysis occurred in 36% and in 20% of the cases respectively, a non-significant difference; however, bleeding occurred more commonly with the regimen involving the longer period of administration (2500 U x7d).…”
Section: Discussionmentioning
confidence: 99%